Rainfall and drought characteristics for crop planning in Palamau region of Jharkhand (MAUSAM, 2014)
Daily rainfall data of 56 years (1956-2011) of Palamau district of Jharkhand have been considered to analyse the long term average and its temporal variability on weekly, monthly, seasonal and annual basis. The average annual rainfall at Palamau was 1138 mm with 34 per cent coefficient of variation indicating thereby that the rainfall was not much stable over the years. July was the highest rainfall recipient month (332 mm) followed by August (310 mm) during the monsoon period. Trend analysis on rainfall of past 56 years exhibited a decreasing pattern of 8.33 mm and 7.04 mm per year in annual and kharif season rainfall, respectively. Agricultural drought was most frequently observed in early (23-26 SMW) as well as late (37-40 SMW) stages of kharif crops. Meteorological droughts of different intensities, viz., mild, moderate and severe over the observed periods showed that station is prone to mild-moderate type of drought. Short duration, low water requiring but high value crops like maize, pulses, oilseeds and some vegetables can be opted for this region to minimize the production risk.